A Systematic Literature Review of Integration of Blockchain and Artificial Intelligence - Ekramifard, Ala; Amintoosi, Haleh; Seno, Amin Hosseini; Dehghantanha, Ali; Parizi, Reza M. (Blockchain Cybersecurity, Trust and Privacy, 2020)
Blockchain and artificial intelligence (AI) have gain the most research attention during recent years. Blockchain is a distributed ledger of trustworthy digital records shared by a network of participants. Blockchain technology has the potential capacity in many fields such as international payment, secure data sharing and marketing, and supply chain management. On the other side, Artificial Intelligence (AI) is used to develop the creation of machines capable of performing tasks that need intelligence. This paper aims to determine the current state of the art within the field of AI with Blockchain technology. In particular, we investigated the latest articles on this integration and carried out an analysis to determine what applications can benefit from it. We identified 23 articles that comply with the assessment criteria. The review research demonstrates that distributed management, security and efficiency improvement, prediction and decision making are among the most popular types of applications that benefit from the integration of AI and Blockchain, while security is the hottest topic. In general, AI algorithms can improve Blockchain design and operation. The combination of these two technologies increases security, efficiency and, productivity of applications.